(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the quality of table beet (Beta vulgaris) as a function of potassium source. The experiment was conducted at the Federal University of Viçosa - Campus Rio Paranaíba - MG. Two experiments were carried out in the summer and winter seasons and with the same experimental matrix. The sources studied were potassium chloride, potassium sulfate, and potassium nitrate. The doses of K were 60, 120, and 240 mg/dm³ of K. The additional treatment was the control without K application. The factors under study were combined in a factorial scheme (3 x 3) + 1 and distributed in blocks to the random with six repetitions. The quality was positively altered by fertilization with K, regardless of the applied sources. Fertilization with K resulting in higher acidity, better firmness, higher L* A and B color intensity, and a linear increase in sucrose. After storage, these variables were reduced in roots without K fertilization and kept when there was fertilization. The quality of roots (soluble solids, texture, and sucrose) of plants grown in winter was higher than in summer crops, with no significant influence of the K source. After being stored, the roots of plants grown in winter showed increased concentration of sucrose, color intensity (L*), acidity, and soluble solids as a function of doses. Thus, it is concluded that K sources do not have significant effects on quality at harvest and after storage in table beets. These variables are increased by potassium fertilization independently of the applied source.